Resurrecting the chimera: Progressions in parenting and peer processes. (18th July 2016) - Forgatch, Marion S.; Snyder, James J.; Patterson, Gerald R.; Pauldine, Michael R.; Chaw, Yvonne; Elish, Katie; Harris, Jasmine B.; Richardson, Eric B.
Abstract: This report uses 6-year outcomes of the Oregon Divorce Study to examine the processes by which parenting practices affect deviant peer association during two developmental stages: early to middle childhood and late childhood to early adolescence. The participants were 238 newly divorced mothers and their 5- to 8-year-old sons who were randomly assigned to Parent Management Training—Oregon Model (PMTO ® ) or to a no-treatment control group. Parenting practices, child delinquent behavior, and deviant peer association were repeatedly assessed from baseline to 6 years after baseline using multiple methods and informants. PMTO had a beneficial effect on parenting practices relative to the control group. Two stage models linking changes in parenting generated by PMTO to children's growth in deviant peer association were supported. During the early to middle childhood stage, the relationship of improved parenting practices on deviant peer association was moderated by family socioeconomic status (SES); effective parenting was particularly important in mitigating deviant peer association for lower SES families whose children experience higher densities of deviant peers in schools and neighborhoods. During late childhood and early adolescence, the relationship of improved parenting to youths' growth in deviant peer association was mediated by reductions in the growth of delinquency during childhood; higher levels of early delinquency are likely to promote deviant peer association through processes of selective affiliation and reciprocal deviancy training. The results are discussed in terms of multilevel developmental progressions of diminished parenting, child involvement in deviancy producing processes in peer groups, and increased variety and severity of antisocial behavior, all exacerbated by ecological risks associated with low family SES.